Estimation of the potential impact of diffuse pollution (non-point source pollution) by simplified methods in the Area of Protection of Flora and Fauna, Pico de Tancítaro, Michoacán, Mexico - Ortiz-Rivera, Alberto (2020)
In this work, the Modified Nonpoint Pollution Index (MPNPI) was calculated in the Area of Protection of Flora and Fauna, Pico de Tancítaro, Michoacán, for three years with different precipitation conditions 2004, 2007 and 2014; this area accommodates 16 basins of the region, within these, 10 localities are representing the physical-geographic typology of the state of Michoacán. MPNPI index calculation requires four indicators: land use (LCI), runoff (ROI), distance (DI) and annual precipitation (API). The results indicate that basins categorized as ranging from medium to very high diffuse contamination potential (nonpoint source pollution potential), with spatial coincidence during the three considered years, are Chuanito, Chondo and Cutio to the northwest; San Francisco and Huandiestacato to the north; Apo and Cuenca Rodada to the west; which in turn cross physical-geographical localities XLIV, XVII and LX; such conjunction allows to delimit spaces with homogeneous environmental characteristics within the basin which, in turn, helps to prioritize units that need to implement mitigation measures against diffuse pollution of aquatic systems